2020
DOI: 10.3390/genes11070820
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Analysis Reveals Localization-Associated Alternative Splicing across 13 Cell Lines

Abstract: Alternative splicing, a ubiquitous phenomenon in eukaryotes, is a regulatory mechanism for the biological diversity of individual genes. Most studies have focused on the effects of alternative splicing for protein synthesis. However, the transcriptome-wide influence of alternative splicing on RNA subcellular localization has rarely been studied. By analyzing RNA-seq data obtained from subcellular fractions across 13 human cell lines, we identified 8720 switching genes between the cytoplasm and the nucleus. Con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 83 publications
(98 reference statements)
3
9
0
Order By: Relevance
“…In PDAC, we observed that oncogenes are enriched in the set of genes that undergo differential IR between clusters IR-1 and IR-2. These findings would be consistent with a model in which failure to remove introns in oncogenes in IR-2 results in intron-containing transcripts that are detained in the nucleus and accumulate, a finding consistent with previous studies 47 50 . This would result in lower functional levels of the encoded tumor-promoting onco-proteins in IR-2 (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In PDAC, we observed that oncogenes are enriched in the set of genes that undergo differential IR between clusters IR-1 and IR-2. These findings would be consistent with a model in which failure to remove introns in oncogenes in IR-2 results in intron-containing transcripts that are detained in the nucleus and accumulate, a finding consistent with previous studies 47 50 . This would result in lower functional levels of the encoded tumor-promoting onco-proteins in IR-2 (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…For these 24 RBP genes, intron retention levels and gene expression levels were both higher in IR-2 compared to IR-1 [47][48][49] . This may reflect an increased contribution to gene expression of poorly spliced transcripts that accumulate in the nucleus in IR-2, as has been observed in other systems [47][48][49][50] . This buildup of IR-containing transcripts in the nucleus in IR-2 could lower the production of functional RBP proteins in the cytoplasm.…”
Section: Role Of Rbps In Differential Intron Retention Between Ir Clumentioning
confidence: 55%
“…The decision of whether an RNA is translated, modified, preserved, or degraded, is dictated by the intracellular location of the RNA, which in turn determines the biological function of the RNA [ 110 ]. Subcellular targeting can, therefore, have a significant influence on the regulatory and biochemical potential of the translated protein.…”
Section: Abiotic Stressmentioning
confidence: 99%
“…This association to ribosomes indicates that JPX transcripts can exit the nucleus, which contrasts what has previously been reported. One possibility that would reconcile the mostly nuclear localization of JPX and other nuclear lncRNAs with ribosome binding lies upon the alternative splicing of RNAs, which often results in multiple isoforms with possibly diverse cellular localizations (Yoshimoto et al 2017;Zeng and Hamada 2020). Indeed, for some lncRNAs highlighted here, significant association to ribosomes of specific splice variants was found exclusively in VCaP ER , hinting at potential mechanisms of nuclear export or ribosome binding exclusive to these isoforms.…”
Section: Discussionmentioning
confidence: 90%
“…We next asked what drives a nuclear lncRNA, such as JPX, to be shuttled into the cytoplasm to be translated. One possibility resides in the production of alternative isoforms for these lncRNAs, for which the subcellular localization could be cytoplasmic, a process under increasing scrutiny for various RNAs (Zeng and Hamada 2020;Yoshimoto et al 2017), which could lead to the production of peptides. We found that some lncRNAs with high TE ratios such as JPX, LINC00467 and WARS_AS1, showed several events of alternative splicing in VCaP ER (Fig.…”
Section: Enz-resistance Is Linked To Aberrant Long Non-coding Rna Association To Ribosomesmentioning
confidence: 99%